A mini-review on the determinants and risk factors of adolescent pregnancy in developing countries - Sulaiman, Shameer Khan; Idris, Idayu Badilla; Hod, Rozita; Abdullah, Nik Nairan; Hod, Rafidah; Shamsusah, Nadia Aqilla (Faculty of Medicine and Health Sciences UPM, 2023)
Pregnant adolescents have been shown to have a higher incidence of health and non-health-related complications that affect both mothers and infants. These include increased risk of pregnancy-related diseases such as anemia and pre-eclampsia, preterm and low-birth-weight babies, as well as other social consequences such as educational and financial difficulties. This mini review evaluates selected articles which explain the attitudes, knowledge, behavior and other risk factors associated with pregnancy among adolescents in developing countries. It also revealed that inadequate knowledge among adolescents about reproductive and sexual health, other social, cultural and peer influences, parenting values, and poor financial and educational status were factors that contribute to adolescent pregnancy. Likewise, a lack of support from parents, educators and healthcare workers had negative impacts on healthy sexual behavior among adolescents, which may ultimately lead to adolescent pregnancy. We conclude that the factors discussed in this review need to be evaluated and taken into consideration by policymakers and healthcare workers when formulating strategies to prevent pregnancies among adolescents.